Time course of recovery is similar for the back squat, bench press, and deadlift in well-trained males - Belcher, D. J.; Sousa, C. A.; Carzoli, J. P.; Johnson, T. K.; Helms, E. R.; Visavadiya, N. P.; Zoeller, R. F.; Whitehurst, M.; Zourdosa, M. C. (Applied Physiology, Nutrition, and Metabolism, 2019)
This study examined the time course of recovery following resistance exercise sessions in the back squat, bench press, and deadlift. Twelve well-trained males (age: 24.5 ± 3.8 years, body mass: 84.01 ± 15.44 kg, training age: 7.1 ± 4.2 years) performed 4 sets to failure at 80% of a 1-repetition maximum (1RM) on the squat, bench press, and deadlift in successive weeks. The bench press was always performed in week 2 with the squat and deadlift order counterbalanced between weeks 1 and 3. Indirect muscle damage and performance fatigue was assessed immediately before and after exercise and at 24 h, 48 h, 72 h, and 96 h postexercise. Outcome measures included limb swelling, joint range of motion, delayed onset muscle soreness, average concentric velocity (ACV) at 70% of 1RM, creatine kinase, lactate dehydrogenase, and cell-free DNA (cfDNA). Most measures demonstrated a main time effect (p < 0.05) within conditions; however, no between condition (p > 0.05) differences existed. ACV decreased in the squat condition for up to 72 h (p = 0.02, -8.61%) and in the bench press (p < 0.01, -26.69%) immediately postexercise but did not decline during the deadlift condition (p > 0.05). There was a main time effect for increased cfDNA in the squat (p < 0.01) and bench press (p < 0.05), but not the deadlift (p = 0.153). Further, immediately postexercise increases in cfDNA were directly related (p < 0.05) to changes in ACV in all 3 conditions. These results suggest that the deadlift does not result in greater muscle damage and recovery time than the squat and bench press following volume-type training in well-trained men. Further, acute changes in cfDNA may predict performance during the recovery period.